Assessment Rainfall-Induced Landslides Using Arbitrary Dipole–Dipole Direct Resistivity Configuration - Mingxin Yue; Guanqun Zhou (Applied Sciences)
Landslides are one of the primary geological disasters posing significant threats to life and property. Strengthening the monitoring of rainfall-induced landslides is, therefore, crucial. The Direct Resistivity (DC) method can accurately map the subsurface electrical resistivity distribution, making it an essential tool for predicting the position of the slide face. However, when conducting landslide surface DC surveys, various undulating terrains such as ridges and steep slopes often pose accessibility challenges. In such topographies, conventional regular grid measurements become very difficult. Additionally, when the terrain is highly undulating and complex, interpreting apparent resistivity data can lead to erroneous results. In this study, we propose using the DC method to monitor rainfall-induced landslides. By moving away from traditional device setups and utilizing an arbitrary dipole–dipole observation system, we aim to improve efficiency, enhance data resolution, and reduce costs. The resistivity of the slope was found to change significantly during the incubation, formation, and development of a landslide in physical model experiments. Furthermore, the feasibility of our proposed method for assessment rainfall-induced landslides was illustrated by a real case study in South China.